Sejarah Teori Peluang dan Statistika - Anggoro, Bambang Sri (Universitas Islam Raden Intan Lampung, INDONESIA, 2015)
Opportunity theory is a branch of mathematics concerned with opportunities, analysis of random phenomena. The main objects of opportunity theory are random variables, stochastic processes, and events: a non-deterministic mathematical abstraction of measurable events or quantities that can be either single events or develop over time in seemingly random modes. If individual coins throw or dice rolls are considered random events, then if repeated sequences of random events will show certain patterns, which can be learned and predicted. Two representative mathematical results illustrating such patterns are the laws of large numbers and the central limit theorem. As a mathematical basis for statistics, probability theory is important for many human activities that involve quantitative analysis of large sets of data. The method of opportunity theory also applies to complex system descriptions given only partial knowledge of their country, as in statistical mechanics. A great discovery of twentieth-century physics is the nature of probability of physical phenomena on the atomic scale, described in quantum mechanics.